74 A pilot inter-professional simulation day for general medical registrars and advanced nurse practitioners covering conditions commonly presenting in older people. (17th November 2016) - McGowan, T; Pattinson, J; Ehilawa, P; Blundell, A; Gordon, A; Woodier, N; Fores, M
Abstract : Background: Patients aged over 65 comprise 65% of admissions to acute hospitals, with most initially managed by healthcare professionals without specific training in care of older people. Simulation can improve knowledge in conditions commonly presenting in, and improve attitudes towards, older people. We developed a novel inter-professional simulation day for general medical registrars and advanced nurse practitioners covering conditions commonly presenting in older people. Methodology: Five scenarios were designed which mapped to the higher specialist training general internal medicine curriculum and covered topics of delirium, elder abuse, fractured pubic ramus, end of life communication and polypharmacy. An additional interactive workshop was included to cover some challenging ethical and legal aspects. Stations ran in two concurrent circuits, with three registrars and 3 ANPs on each, using both simulated patients and manikins. The day has so far run twice, with both consultant geriatricians and a nurse educator in care of older people attending as faculty to conduct structured debriefs after each scenario. Results: 19 of the 20 participants stated they would recommend the day to colleagues and that the day was pitched at the appropriate level of difficulty, with comments including "very challenging and taken out of comfort zone – however I got more from the sessions due to this". Following the day, participants scored on average 1.4 points higher (P < 0.05) on a 10 point knowledge test and 1.2 marks higher in the team-working aspect of the Readiness for Inter-Professional Learning Scale (RIPLS) (P < 0.05) . Changes to other domains in RIPLS were not statistically significant. Potential impact: An inter-professional geriatric simulation day for general medical registrars and ANPs is feasible, well-received, and improves knowledge and inter-professional team-working. Two further days with further analysis will help enable us to complete a more statistically robust analysis and better understand the impact on patient care.